Pendidik dan Peserta Didik Dalam Perspektif Islam - Difa'ul Husna; Yazida Ichsan; Unik Hanifah Salsabila (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2020)
Education is a conscious effort in creating conditions and situations that support the learning process, potential development and personality formation. Ideally educators and learners have the ability to maintain adab and understand their respective rights and obligations. But in recent years there have been cases involving educators and learners, who have harmed the world of education and obscured the positions and roles of educators and learners. The focus of the study in this qualitative research is limited around islamic perspectives towards educators and learners. Based on some literature, it is known that in Islam there are four subjects categorized as educators. The main task of educators is to bring the hearts of students to Allah SWT through various learning methods. The learner is someone who intends to develop his potesi through the guidance and education process of the adults around him, sehigga he becomes someone who is well-known, faith-fearing and noble, improves his quality of life and performs his duties as a man and caliph. Related to that, educators and learners have several conditions and characteristics that are fused in their personality and realized in each of their deeds.